Complex biliary stones management: cholangioscopy versus papillary large balloon dilation – a randomized controlled trial - Franzini, Tomazo; Moura, Renata Nobre; Bonifácio, Priscilla; Luz, Gustavo Oliveira; de Souza, Thiago Ferreira; dos Santos, Marcos Eduardo Lera; Rodela, Gustavo Luis; Ide, Edson; Herman, Paulo; Montagnini, André Luis; D’Albuquerque, Luiz Augusto Carneiro; Sakai, Paulo; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2018)
Background and study aims Endoscopic removal of biliary stones has high success rates, ranging between 85 % to 95 %. Nevertheless, some stones may be challenging and different endoscopic methods have evolved. Papillary large balloon dilation after sphincterotomy is a widely used technique with success rates ranging from 68 to 90 % for stones larger than 15 mm. Cholangioscopy allows performing lithotripsy under direct biliary visualization, either by laser or electrohydraulic waves, which have similar success rate (80 % – 90 %). However, there is no study comparing these 2 techniques. Patients and methods From April 2014 to June 2016, 100 patients were enrolled and randomized in 2 groups, using a non-inferiority hypothesis: cholangioscopy + electrohydraulic lithotripsy (group 1) and endoscopic papillary large balloon dilation (group 2). The main outcome was complete stone removal. Adverse events were documented. Mechanical lithotripsy was not performed. Failure cases had a second session with crossover of the methods. Results The mean age was 56 years. 74 (75.5 %) patients were female. The initial overall complete stone removal rate was 74.5 % (77.1 % in group 1 and 72 % in group 2, P > 0.05). After second session the overall success rate achieved 90.1 %. Procedure time was significantly lower in group 2, – 25.2 min (CI95 % – 12.48 to – 37.91). There were no significant differences regarding technical success rate, radiologic exposure and adverse events. Conclusion Single-operator cholangioscopy-guided lithotripsy and papillary large balloon dilation are effective and safe approaches for removing complex biliary stones.